Engineered Ultrasmall Nanoparticle Drug‐Immune Conjugates with "Hit and Run" Tumor Delivery to Eradicate Gastric Cancer. Issue 3 (14th November 2022) - Zhang, Li; Aragon‐Sanabria, Virginia; Aditya, Anusha; Marelli, Marcello; Cao, Tianye; Chen, Feng; Yoo, Barney; Ma, Kai; Zhuang, Li; Cailleau, Thais; Masterson, Luke; Turker, Melik Z.; et al.
Abstract: Despite advances by recently approved antibody‐drug conjugates in treating advanced gastric cancer patients, substantial limitations remain. Here, several key obstacles are overcome by developing a first‐in‐class ultrasmall (sub‐8‐nanometer (nm)) anti‐human epidermal growth factor receptor 2 (HER2)‐targeting drug‐immune conjugate nanoparticle therapy. This multivalent fluorescent core–shell silica nanoparticle bears multiple anti‐HER2 single‐chain variable fragments (scFv), topoisomerase inhibitors, and deferoxamine moieties. Most surprisingly, drawing upon its favorable physicochemical, pharmacokinetic, clearance, and target‐specific dual‐modality imaging properties in a "hit and run" approach, this conjugate eradicated HER2‐expressing gastric tumors without any evidence of tumor regrowth, while exhibiting a wide therapeutic index. Therapeutic response mechanisms are accompanied by the activation of functional markers, as well as pathway‐specific inhibition. Results highlight the potential clinical utility of this molecularly engineered particle drug‐immune conjugate and underscore the versatility of the base platform as a carrier for conjugating an array of other immune products and payloads. Abstract : A tunable first‐in‐class ultrasmall fluorescent core–shell silica nanoparticle, bearing site‐engineered anti‐human epidermal growth factor receptor 2 (HER2) single chain variable fragments and topoisomerase inhibitors, eradicates HER2‐expressing gastric tumors via a "hit and run" approach without tumor regrowth. Its favorable target‐specific uptake and penetration, pharmacokinetic profile, and wide therapeutic index highlight its potential clinical utility for theranostic applications.